The Effect of ST 37 Steel Roughness in The Turning Process with Oil Cooling Media to Variation of Spindle Speed and Type of Tools: Pengaruh Kekasaran Baja ST 37 pada Proses Pembubutan dengan Media Pendingin Oli Terhadap Variasi Kecepatan Spindle dan Jenis Pahat - Syaiful Syaiful (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2023)
The development of increasingly advanced and modern technology in the industrial sector, both machine tools and metallurgical machines, plays a very important role in the industrial world. The specimens in this study were ST 37 steel whose roughness value would be determined through a turning process using HSS and carbide chisels with oil-cooling media, as well as different machine rotation speeds, where the specimens were turned at machine spindle speeds of 330 rpm, 660 rpm, and 900 rpm. Then tested for roughness using a Surface Roughness Tester machine. The results of the analysis yield the lowest roughness average of the R-curve (Ra) (smooth facing) at a spindle speed of 900 rpm using a carbide chisel and the highest Ra (coarse facing) at a spindle speed of 330 rpm using an HSS chisel, from the roughness value obtained, then macro photo testing is carried out to see the structure of the material more closely. The results of this study indicate that the roughness value is influenced by the material, speed variation, type of tool and cooling treatment.